2014
DOI: 10.1186/1756-6606-7-24
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming non-human primate somatic cells into functional neuronal cells by defined factors

Abstract: BackgroundThe common marmoset (Callithrix jacchus) is a New World primate sharing many similarities with humans. Recently developed technology for generating transgenic marmosets has opened new avenues for faithful recapitulation of human diseases, which could not be achieved in rodent models. However, the longer lifespan of common marmosets compared with rodents may result in an extended period for in vivo analysis of common marmoset disease models. Therefore, establishing rapid and efficient techniques for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…We recorded voltage-sensitive currents in 30- to 60-day-old TiPSC- and aHDF-iPSC-derived neurons. iPSC-derived neurospheres were infected with a lentivirus expressing human synapsin promoter-driven GFP (CSIV–hSynI-GFP-IRES2-NeoR) ( Zhou et al., 2014 ) and differentiated into neurons. TTX-sensitive voltage-gated membrane currents were indistinguishable between neurons derived from TiPSCs and those derived from aHDF-iPSCs ( Figure S6 A).…”
Section: Resultsmentioning
confidence: 99%
“…We recorded voltage-sensitive currents in 30- to 60-day-old TiPSC- and aHDF-iPSC-derived neurons. iPSC-derived neurospheres were infected with a lentivirus expressing human synapsin promoter-driven GFP (CSIV–hSynI-GFP-IRES2-NeoR) ( Zhou et al., 2014 ) and differentiated into neurons. TTX-sensitive voltage-gated membrane currents were indistinguishable between neurons derived from TiPSCs and those derived from aHDF-iPSCs ( Figure S6 A).…”
Section: Resultsmentioning
confidence: 99%
“…We recorded voltage-sensitive currents in 60-day-old LiPSC-derived neurons to confirm their electrophysiological properties. LiPSC-derived NSs were infected with a lentivirus expressing a human Synapsin I promoter-driven GFP (CSIV–hSynI-GFP-IRES2-NeoR) soon after single dissociated NS cells were plated [ 27 ]. After neuronal maturation, voltage-dependent Na + and K + currents and TTX-sensitive voltage-gated membrane currents were detected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, specific culture conditions have been developed to maintain the pluripotent stem cells (PSCs) in an extended PSC stage (EPSC) with widespread chimeric contribution to embryonic and extraembryonic lineages in vivo [ 28 ]. The derivation and tendency of the marmoset pluripotent stem cells to differentiate into neural lineages has been reported [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] using variable techniques for the neuralization based on the initial protocol developed for human embryonic stem cells [ 38 , 39 , 40 , 41 , 42 , 43 ]. In this study, we demonstrated that using the NN1 medium supplemented with growth factors, we were able to isolate NSCs that are responsive to mitogenic growth factor.…”
Section: Discussionmentioning
confidence: 99%